Innovación y Liderazgo - Chavarria, Randy (2024)
This article is about innovation and leadership, which are two fundamental aspects that drive the success and competitiveness of organizations in today's business environment. Innovation refers to the generation and application of new ideas, methods, products or services that add value and make a difference in the market. For its part, leadership is related to the ability to influence, inspire and guide the members of an organization towards the achievement of common objectives. The relationship between innovation and leadership is bidirectional. On the one hand, innovation requires leaders who create an environment conducive to idea generation and experimentation. On the other hand, effective leadership thrives on innovation, as it allows organizations to adapt to change, differentiate themselves from the competition, and generate sustainable value.